Life skills activities for secondary students with special needs - Mannix, Darlene (West Nyack, N.Y. : Center for Applied Research in Education, 1995)
Interpersonal skills. Communication skills. Academic and school skills. Practical living skills. Vocational skills. Lifestyle choices. Problem-solving skills.
Keywords: Education; Teaching; Handicapped teenagers; Handicapped teenagers -- United States -- Life skills guides; Life skills -- Study and teaching (Secondary) -- United States; Life skills -- United States -- Problems, exercises, etc